The Influence of Parenting Patterns and Teacher Personality on Learning Motivation of Children At Sondakan State Elementary School - Edofeyuda, Alfian; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to explore the influence of parenting patterns and teacher personality on student learning motivation at SD Negeri Sondakan. The primary objective is to determine the extent to which these two factors affect student motivation in an elementary school setting. Methodology: This research employed a quantitative approach with a survey design. A total of 200 students from SD Negeri Sondakan participated as respondents. Data were collected through questionnaires covering three main variables: learning motivation, parenting patterns, and teacher personality. Descriptive statistical analysis was conducted to provide an overview of the data, while multiple linear regression analysis was used to examine the effect of each independent variable on the dependent variabl. Results: The results of the multiple linear regression analysis revealed that both parenting patterns and teacher personality had a positive and significant effect on student learning motivation. The regression coefficient for parenting patterns was 0.532, and for teacher personality, it was 0.761. Teacher personality was found to have a stronger influence on student motivation than parenting patterns. Applications/Originality/Value: This study highlights the critical role of teacher personality in fostering student motivation in the classroom. It underscores the importance of quality teacher-student interactions and calls for strong collaboration between parents and teachers to build an optimal learning environment. The findings offer valuable insights for educational practitioners aiming to enhance student engagement and academic performance in elementary schools.